Pencobaan Di Tengah Kelimpahan : Analisis Teologis Terhadap Kitab Bilangan 11:31-35 - Sefi Taberima; Analisman Laoli (Teokristi: Jurnal Teologi Kontekstual dan Pelayanan Kristiani, 2026)
Temptation amidst abundance are two conditions often experienced by every believer, where in the abundance of blessings, there are also temptations if they cannot manage those blessings properly. This study was conducted with the aim of understanding what is meant by temptation amidst abundance according to the book of Numbers 11:31-35 and to analyze the theological content contained therein. The topic of temptation amidst is a research that has a slow development rate so that it allows for a more in-depth study. Therefore, this study was examined using grammatical-historical exegesis and exposition methods of the text. Based on the results of the study, it was found that God truly gives according to the right time, everyone must learn to control themselves so as not to be dragged into lust, because there are always consequences for every action taken. Keys Word: Quail, Plague, Wrath of God, Kibrot-Taawa